O impacto dos poços artesianos na qualidade dos lençóis freáticos na cidade de Manaus e a legislação vigente - Lima, Wendell De Araújo (2016)
This work was a concern, due to the State's failure to not supervising of the drilling of wells in the city of Manaus, despite having legislation that deals with the management of water resources in the State of Amazonas. The State of Amazonas through the law n. 3167/07, regulates the State Water Resources Policy and establishes the State System of Management of the State of Amazonas Water Resources. The unbridled drilling and lack of oversight has caused damage which may become irreparable to groundwater in the city of Manaus. The objective of this research is investigate, with the agencies responsible for management (execution / supervision), among others such as: Department of the State of Amazonas Environment, Institute of Environmental Protection of Amazonas (IPAAM), State Council for Water Resources Amazon, the Amazon River Basin Committees, the Water agencies of State of Amazonas , CPRM and the Manaus dealership Environmental, and what is occurring, to carry effectively the law, to equate this omission. The methodology used, will be done through the study of current legislation (quantitative) and interviews (qualitative) in various organs above mentioned.